1996
DOI: 10.1128/cdli.3.1.14-22.1996
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of human placental trophoblast subpopulations from first-trimester chorionic villi

Abstract: A method for the simultaneous preparation of highly enriched human placental trophoblast populations (villous and extravillous) from first-trimester placental villi (5 to 12 weeks) by using sequential trypsinization, percoll gradient centrifugation, and negative selection with anti-CD9 immunomagnetic separation is described. The purification method resulted in the isolation of four distinct trophoblast populations identified on the basis of morphology and phenotyping: (i) mononuclear villous cytotrophoblast ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 30 publications
(29 reference statements)
1
21
0
Order By: Relevance
“…Trophoblast invasion of the maternal uterus during human placentation is a highly complex process that involves cell proliferation, migration, and cell differentiation. Several known factors have been described in human syncytiotrophoblasts, including the Wnt genes (Nusse and Varmus 1992), the Hox gene (Oudejans et al 1990;Taylor et al 1997), and the integrin family (Yang et al 1995;Aboagye-Mathiesen et al 1996). In this study we have characterized a member of the human Gcm gene family and have demonstrated that the h Gcm 1 gene, like its mouse homologue, is also expressed in placenta.…”
Section: Discussionmentioning
confidence: 61%
“…Trophoblast invasion of the maternal uterus during human placentation is a highly complex process that involves cell proliferation, migration, and cell differentiation. Several known factors have been described in human syncytiotrophoblasts, including the Wnt genes (Nusse and Varmus 1992), the Hox gene (Oudejans et al 1990;Taylor et al 1997), and the integrin family (Yang et al 1995;Aboagye-Mathiesen et al 1996). In this study we have characterized a member of the human Gcm gene family and have demonstrated that the h Gcm 1 gene, like its mouse homologue, is also expressed in placenta.…”
Section: Discussionmentioning
confidence: 61%
“…This is because such samples are likely to contain multiple other cells types, in addition to trophoblasts including fibroblasts and vascular cells. One alternative to our approach would be to selectively purify trophoblasts from placental villus tissue (Aboagye-Mathiesen et al, 1996). However, we were concerned that such procedures involved would severely limit the availability of DNA for down stream molecular analysis and we also wished to avoid potential process-dependent modification of the epigenetic signature.…”
Section: Discussionmentioning
confidence: 99%
“…Normal placental development depends on the ability of EVTs to attach to and then invade into the maternal decidua and the first third of the myometrium. This occurs in order to anchor the fetus to the maternal endometrium and then invade the maternal spiral arteries creating large-diameter, low resistance vessels that provide a means of steady perfusion of the floating villi with maternal blood ( Genbacev et al ., 1992 ; Irving et al ., 1995 ; Aboagye-Mathiesen et al ., 1996 ). Insufficient trophoblast invasion of the spiral arteries has been associated with pre-eclampsia and fetal growth restriction ( Hustin et al ., 1990 ; Kadyrov et al ., 2006 ).…”
Section: Introductionmentioning
confidence: 99%